The efficiency of distress thermometer in the determination of supporting needs for cancer inpatients. Issue 1 (1st January 2021) - Al-Shaaobi, Abdullah; Alahdal, Murad; Yu, Shiying; Pan, Hongming
ABSTRACT: Psychological distress scale is highly recommended for cancer patients' care. Several psychological scales have been implemented in cancer outpatient clinics. However, the use of the psychological distress scale, particularly distress thermometer (DT), in the inpatient has not been reported. In this study, we report the efficacy of DT in the determination of cancer inpatients' supporting needs. A total of 170 inpatients diagnosed with cancer have been enrolled in this study. Only 132 patients matched the inclusion criteria, while other cases were excluded because of other diseases associated with cancer. The standardized problem list (PL) and Hospital Anxiety and Depression Scale (HADS) were implemented in comparison with DT. Then, the cut-off score of DT was performed to identify clinically significant differences. The analysis of the receiver operating characteristic (ROC) curve revealed that a DT cut-off score of 4 displayed 0.76 under the ROC curve. Sensitivity showed 0.86 sensitivity for cut-off score 4 and a specificity of 0.56 relative to the HADS cut-off score (≥15). DT scores were found independent of medical variables such as cancer type and stage, recurrence, or metastasis. Clinical ECOG-SP showed a significant association with the DT cut-off score (P ≤ 0.05). Regarding PL, patients with scores above DT cut-off were suffering 21 of 40 problems in all categories. Furthermore, patients that scored above the DT cut-off significantly showed an association with high support needs. DT scale showed significant performance in the evaluation of psychological distress among cancer inpatients through the efficient determination of their support needs.